Nietzsche on tragedy - Silk, M. S. (C. U. P, 2016)
The first comprehensive study of Nietzsche's earliest book, The Birth of Tragedy (1872), this important volume by M. S. Silk and J. P. Stern examines the work in detail: its place in Nietzsche's philosophical career; its value as an account of ancient Greek culture; its place in the history of German ideas, and its value as a theory of tragedy and music. Presented in a fresh twenty-first-century series livery, and including a specially commissioned preface written by Lesley Chamberlain, illuminating its enduring importance and relevance to philosophical enquiry, this accessible study has been revived for a new generation of readers.